Everyday life, consumption and urban life in middle-sized Brazilian cities - Goes, Eda Maria [UNESP] (Revues Org, 2016)
Assuming that consumption is the meaning from which the spatial practices can be learned today, the perspective of analysis adopted in this article is the Geography of everyday life, that values the role of each townsman as a subject in the urban space production process, which led us to carry out a series of 89 interviews with residents of six middle-sized Brazilian cities (Marilia, Presidente Prudente, Ribeirao Preto, Sao Carlos and Sao Jose do Rio Preto at Sao Paulo State, and Londrina at Parana State). Based on its analysis, the struggles waged on consumption and the key role of spaces were evidenced, observing that the house, its equipment and the individual vehicle structure a permanent and renewable object system, which assumed autonomy and operates in the reproduction of social inequalities. As main conclusion it is observed that the expansion of access to the housing market, household appliances and vehicles occurred in Brazil since the 1990s, mainly in the 2000s, made possible the spread of the working class representation, as a consumer and producer of urban life at the same time that normalization of the consumption, individual leisure and the peripheral location of residences have favored social control, especially in these middle-sized cities in which public spaces, trade unions, political manifestations and even the tavern on the corner exercise ever less attraction.
Keywords: consumption; everyday life; middle-sized cities; social control